Biomechanical report for the IAAF World Indoor Championships 2018 long jump men - Tucker, C.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2019)
The men`s long jump took place on the evening of Friday 2nd March. It was a fiercely contested event with Cuba`s Juan Miguel Echevarría emerging victorious at the end over the current World Champion, Luvo Manyonga of South Africa. There was a mere four centimetres separating the medallists in a compelling contest. From the opening round Echevarría led, however Manyonga took the lead in the third round with a jump of 8.33 metres. Manyonga further improved on this jump in round 4 with an effort of 8.44 metres. Echevarría responded in the fifth round with a leap of 8.46 metres to take the lead, a lead that would not be relinquished in the final round. Marquis Dendy finished in third place with a fifth round jump of 8.42 metres, just four centimetres short of the winning jump.